1995
DOI: 10.1002/recl.19951141103
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐state intramolecular charge transfer in donor/acceptor‐substituted aromatic hydrocarbons and in biaryls. The significance of the redox potentials of the D/A subsystems

Abstract: Abstract. The energy of the charge transfer (CT) emission maximum of a series of dual fluorescent 4-aminobenzonitriles in diethyl ether and acetonitrile does not show a correlation with the redox potentials of the amino (D) and benzonitrile (A) subgroups. It is therefore concluded that these electron donor and acceptor subgroups cannot be treated in the same way as the A and D molecules in exciplexes '(A-D'). This means that in the intramolecular charge transfer (ICT) state of the aminobenzonitriles, a conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 53 publications
9
140
0
Order By: Relevance
“…The hypothesis of TICT states has recently been challenged (Zachariasse et al, 1993;von der Haar et al, 1995); because these arguments are based on experiments with compounds that have been central to the TICT hypothesis (4-aminobenzonitriles), they might be expected to carry over to the case of rhodamines (K. A. Zachariasse, personal communication). The rhodamines and 4-aminobenzonitriles are similar in many respects.…”
Section: Arguments Against Tict Statesmentioning
confidence: 99%
“…The hypothesis of TICT states has recently been challenged (Zachariasse et al, 1993;von der Haar et al, 1995); because these arguments are based on experiments with compounds that have been central to the TICT hypothesis (4-aminobenzonitriles), they might be expected to carry over to the case of rhodamines (K. A. Zachariasse, personal communication). The rhodamines and 4-aminobenzonitriles are similar in many respects.…”
Section: Arguments Against Tict Statesmentioning
confidence: 99%
“…Different models like pseudo-JahnÀTeller interaction of excited states 3,4 and in-plane bending and rehybridization of acceptor 5,6 were proposed for the dual emission of DMABN, but the most accepted one is twisted intramolecular charge transfer (TICT), where a π/2 twist of the donor moiety with respect to the benzene plane is considered to stabilize the ICT state. 7À9 As these types of ICT systems are very sensitive to solvent polarity and viscosity, much research 10,11 is being done to understand and systematize the ICT systems.…”
Section: Introductionmentioning
confidence: 99%
“…3, the fluorescence decay time of OPVCN–C12 in chloroform solution (20°C, τ 1 = 1.47 ns) can be fitted as single exponentials without indication of a locally excited (LE) state. The result demonstrated that an ICT reaction from an LE state to an ICT state probably occurred in the solution (34,35). The decay time of OPVCN–C12 in a mixture of dichloromethane–acetonitrile (v/v, 1:3) solution ( τ 1 = 0.36 ns, single exponentials) was much shorter than that in pure chloroform solution, which indicated the existence of unstable excited states and stronger intramolecular charge transfer process in OPVCN–C12 in a dichloromethane–acetonitrile (v/v, 1:3) solution.…”
Section: Resultsmentioning
confidence: 96%